Migration of holes: numerical algorithms and implementation - Breidbach, J; Cederbaum, L S (The Journal of chemical physics, 2007)
A hole created in a system, for instance by ionization, can migrate through the system solely driven by many-electron effects. The implementation of the theory of charge migration and the numerical algorithms used are described in detail. A description of the ab initio calculation of charge migration in realistic systems is presented for several examples and the underlying mechanisms of charge migration are identified and interpreted using theoretical models. In all cases studied the migration is found to be ultrafast.